Mendiagnosa Kerusakan Handphone Menggunakan Aplikasi Sistem Pakar - Dharmawan Hadi Santoso; harjono Harjono (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
Mobile phone is a mobile device that helps people in their daily activities, because mobile phones are so often damaged by mobile phone is dropped, exposed to water or because of the care an duse. This research aims to build a program to build an expert system to detect damage to mobile phones and to suggest repair. In this research applied the method to perform forward chaining observations based on some facts to gain a conclusion. This expert system is a JSP application created using adobe dreamweaver CS3. The results of an expert system consisting of a menu consultation, master data, relationship data, and instructions. This expert system capable of detecting damage to hand phones and give suggestions for repair